Quantitative analysis of idiopathic epiretinal membrane traction: an updated version of the relaxation index - Allegrini, Davide; Raimondi, Raffaele; Montesano, Giovanni; Caruso, Marco; Lionetti, Giovanna; Carnevali, Adriano; Sorrentino, Tania; Scorcia, Vincenzo; Romano, Mario R. (Frontiers in Ophthalmology, 2025)
PurposeThe aim of this work was to track tangential traction of idiopathic epiretinal membrane from an initial assessment to the immediate post-operative phase using an enhanced version of the relaxation index (RI).MethodsA retrospective analysis was conducted on 9 patients who underwent peeling surgery for idiopathic, symptomatic, and progressive epiretinal membrane. The RI assesses the displacement of vascular crossings in time from a fixed point, which is the retinal pigmented epithelium. This updated iteration integrates infrared images paired with OCT scans instead of OCTA.ResultsThe study encompassed three timepoints: T1 (initial appointment), T2 (1 week pre-surgery), and Post (1 month post-surgery). T1 was 12± 9 months prior to surgery. A statistically significant difference (p<0.001) in RI was observed across all three timepoints; however, there was no significant correlation between RI and visual acuity (p>0.05).ConclusionThe RI emerges as a comprehensive and direct parameter for objectively assessing and monitoring tangential traction in three dimensions across an extensive area of the posterior pole. Further streamlining of the process is necessary to integrate this feature into clinical practice effectively.